The Power of Local Authorities in Handling Divorce - Nabila Luthvita Rahma; Supriyadi Supriyadi; Moh Abdul Latif; Rozanah Ab Rahman (Pandecta Research Law Journal, 2026)
This study seeks to describe and analyze the role of local authorities (i.e., village chiefs) in handling divorce, as well as the implications for their involvement for women and households. In so doing, this article investigates how local wisdom-based legal systems are realized. Data were collected through observation, interviews, and a review of the literature. This research shows that divorce occurs when families, as communal and religious units, deal with economic difficulties and social media. The recognition of village chiefs as the sole authorities with the authority to decide legal matters is foundational for the traditional legal system practiced within the community, wherein it is the village chiefs—rather than the religious courts—who may handle divorces. In this capacity, village chiefs act as key mediators for the Madurese people, demonstrating that customary authority operates not merely as a residual practice but as a parallel and socially dominant legal order.This article recommends that future studies employ a formalistic approach to understand the validity of customary law, with a broad range of cases and diverse sources used to create a progressive legal system that is recognized and accepted by society.